A study on etiology of incontinence in double knockout mouse model. Issue 1 (February 2023) - Yadav, Priyank; Farhat, Walid A.; Hijaz, Adonis; Seo, Jiwon; Hui, Chi-Chung; Tuba-Ang, Karen; Mo, Rong; Chua, Michael
Summary: Introduction and objective: Stress urinary incontinence is of concern in both pediatric and adult population. Double mutant GLI family zinc finger Gli2 +/− ; Gli3 Δ699/+ murine model of stress incontinence has been recently developed as a reliable model which does not require surgical manipulation to create incontinence and is shown to survive to adulthood. The aim of this study was to establish the etiology of incontinence in the double mutant Gli2 +/− ; Gli3 Δ699/+ mice. Study design: We used 13 cluster of differentiation 1 (CD-1) mice (7–9 weeks) for demonstration of histology of the bladder and urethra. There were 3 Wild Gli2 +/- females, 2 Wild Gli2 +/- males, 4 Gli2 +/- ;Gli3 Δ699/+ females and 4 Gli2 +/- ;Gli3 Δ699/+ males. The Wild Gli2 +/- mice served as the control group and Gli2 +/- ;Gli3 Δ699/+ mice served as the test group. Additionally, eight 16.5 days mice (2 each of Wild Gli2 +/- females, Wild Gli2 +/- males, double knockout (DKO) Gli2 +/- ;Gli3 Δ699/+ females and Gli2 +/- ;Gli3 Δ699/+ males) were used to assess the histology of the spinal cord. The gross appearance of bladder and urethra was studied using ink injection assays. Immunohistochemistry was done for smooth muscle actin and cytokeratin. Results: Gross and histologic appearance confirmed the previously reported widening of bladder outlet and hypoplasia of smooth muscles in female urethra and also established them in the male urethra of Gli2 +/- ;Gli3 Δ699/+ mice compared to Gli2 +/- mice. The double knockout mice were smaller than the Gli2 mice (5.2 vs 6.1 cm, p = 0.002). Immunohistochemistry demonstrated epithelial hyperplasia and smooth muscle hypoplasia. Additionally, there was prostatic hypoplasia in the Gli2 +/- ;Gli3 Δ699/+ male mice. The spinal cord length for body size appeared comparable between the Gli2 +/- and Gli2 +/- ;Gli3 Δ699/+ mice but histological evaluation revealed abnormal development of the caudal end of the vertebral body with premature termination of the spinal cord (Figure). Discussion: The histological changes in the bladder neck and urethra were consistent to those previously reported. While previous report described the findings in female mice only, we confirmed that these findings are also present in males as well as prostatic hypoplasia, a possible additional factor leading to stress incontinence. The most important finding in the present study however, was the detection of premature termination of spinal cord in the DKO Gli2 +/− ; Gli3 Δ699/+ mice which has not been reported previously and is likely a major contributor to incontinence in this model. Conclusion: The incontinence in male as well as female Gli2 +/− ; Gli3 Δ699/+ mice is due to both myogenic and neurogenic involvement. These double knockout mice are a valuable model of stress incontinence related to neurogenic bladder due to low outlet resistance. Summary Figure (a) Gross appearance of the spinal cord in Gli2 +/− ; Gli3 Δ699/+ (left side) and Gli2 +/− (right side) mice showing proportional length for body size. (b) Histological evaluation of 16.5 days Gli2 +/− (left side) and Gli2 +/− ; Gli3 Δ699/+ (right side) mice showing caudal vertebral bodies and spinal cords. Note the difference at the caudal end ( Asterisks denote attachment of tail). Scale bars: 1 mm. Summary Figure